A legal perspective on the role of municipalities in navigating the relationship between land use planning and mining - Van Schalkwyk, Catherine Louie (Department of Private Law, 2019)
The legislative and executive powers dealing with mining and land use respectively are allocated to different spheres of government. Mining rights are issued by the Department of Mineral Resources (DMR), as representative of the national government, whereas land use and zoning are regulated by municipalities, the local sphere of government. According to a 2012 ruling by the Constitutional Court of South Africa, a mining right holder cannot commence mining activities, despite holding the mining right, unless and until the land is appropriately zoned by the municipality in whose jurisdiction the land is located. The separate functions of the two spheres of government make duplication in application processes inevitable. The potential for conflicting decisions is also apparent. This project aims to determine how alignment of the respective processes of obtaining a mining right and land use approval can provide for better co-operation between the responsible government authorities. This question translates into two sub-inquiries: a) How do municipalities currently regulate land use for mining purposes? b) Should municipal rezoning procedures be incorporated into the application process for mining rights? These issues are considered by examining three selected municipalities’ rezoning procedures and policies and comparing these to the requirements of mining right applications. The thesis investigates the extent to which these procedures overlap and are duplicated. Potential policy changes are explored, to suggest streamlining application processes by providing a more cohesive solution. The three selected municipalities are the City of Cape Town Municipality in the Western Cape Province, the Sol Plaatje Municipality in the Northern Cape Province and the City of uMhlathuze Municipality in KwaZulu-Natal Province. The thesis shows how poor intergovernmental relations and processes hamper effective co-operation and collaboration between the DMR and municipalities. While it is imperative that each government institution retains legislative and executive authority over their respective constitutional powers – DMR over mining activities, and municipalities over land use issues – the thesis argues that greater efforts at process alignment or synchronisation are necessary. It offers suggestions for improvement.